2018
DOI: 10.1080/13540602.2018.1527762
|View full text |Cite
|
Sign up to set email alerts
|

Overarching professional identity themes in student teacher workplace learning

Abstract: This study reports on how student teachers learn in the workplace. Data from 10 student teachers were collected by means of digital logs and in-depth interviews. By reconstructing data into stories and unravelling these stories, it became clear that the learning process of each student teacher was dominated by one specific theme, such as student-centred teaching or creating a positive learning climate. These themes could be typified as professional identity themes, because all appeared to be both personal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
3
40
0
6
Order By: Relevance
“…We found that the dramatic changes in these three aspects: technological, pedagogical and educational system blurred the boundaries and gave rise to previously unknown dilemmas and tensions, between the two learning spheres -home and school -and between the personal and the professional aspects (Leeferink, Koopman, and Schellings 2019).…”
Section: Discussionmentioning
confidence: 89%
“…We found that the dramatic changes in these three aspects: technological, pedagogical and educational system blurred the boundaries and gave rise to previously unknown dilemmas and tensions, between the two learning spheres -home and school -and between the personal and the professional aspects (Leeferink, Koopman, and Schellings 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Second, themes were searched for to group the 45 portraits (cf. Leeferink et al 2019;Van Der Wal et al 2019). The portraits were examined to identify preliminary themes in an inductive way, for example, 'cooperation with students' and 'problems with explicating classroom rules'.…”
Section: Discussionmentioning
confidence: 99%
“…Third, correspondence in the preliminary themes was searched for in order to combine them into overarching themes by the same two authors together (Leeferink et al 2019). For example, 'relationship with students', 'cooperation with students', 'order', 'class climate', 'problems with discipline', and 'explicate classroom rules' were summarised by the overarching theme 'Classroom management'.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of the Swedish or Nordic context deal with specific content in teacher education and there has been particular interest in areas like placement (in Sweden this is called VFU) (Hegender, 2010;Jedemark, 2019;Karlsson Lohmander, 2015;Leeferink et al, 2018), degree project (Erixon Arreman & Erixon, 2015;Gustavsson & Eriksson, 2015), and the relationships between theory and practice (Saetra, 2018;Wågsås Afdal & Spernes, 2018). In several studies, Wågsås Afdal has also compared the Finnish TE programme, which has a clear research approach, to the more profession-oriented Norwegian programme to see what consequences these different approaches and organisational perspectives have for the content of teacher education and for the future teachers' knowledge base and professional identity (Wågsås Afdal, 2012, 2017Wågsås Afdal & Nerland, 2014).…”
Section: Previous Researchmentioning
confidence: 99%